A proposed group counseling program for the Oblate Seminary, Cotabato City - Mendiola, Danilo G. (Animo Repository, 1975)
The purpose of this paper was to study the possibility of integrating a group counseling program into the total scheme of seminary education and to propose a feasible group counseling program for the Oblate Seminary in Cotabato City. In order to answer the problems raised in the study concerning the Oblate seminarian himself, his typical profile, his problems and needs as related to group counseling, and his self-actualizing values were assessed by means of the Mooney Problem Check List, an appended questionnaire to the check list, informal interviews, personal observations, and a personality test called the Personal Orientation Inventory. The library method of research was used in determining the environmental background of the proposal the basic philosophy of seminary education the role of the seminary in the education of the seminarians and the nature of group counseling and its place in the seminary. The main respondents in this study are the Oblate seminarians at the Oblate Seminary in Cotabato City. The total population of the seminary is 24, but only 23 participated in the study since one of them came in only during the second semester. For the purpose of comparing their self-actualizing values with those of non-seminarians, a group of college students matching the seminarians in year-level, age and IQ was randomly chosen from the male population of Notre Dame University. The subjects of this study were also compared with a group of older Oblate seminarians, novices and scholastics that have had the same seminary training as the main respondents. Findings from the various works of authorities on group counseling and seminary education indicated that group counseling, with its growth potential and appeal especially among adolescents, could contribute much to the total personal growth of the seminarians. Thus, a group counseling program integrated into the present set-up of the Oblate Seminary in Cotabato City was proposed. The main highlights of the proposal included a three-phase program consisting of a maximum of 15 sessions to last for a semester. The three phases of the program were such that they follow the normal developmental stages of a group, namely : the establishment stage, the transition stage, and the closing stage. The contents of the sessions were also planned to include discussions of the problems brought out by the seminarians in the pre-survey.